Unclosed wound: effect of childhood access to healthcare on cardiovascular health trajectories of Chinese older adults based on entropy balancing analysis - Mao, Boshu; Fang, Xiaoyi; Liu, Lingjun (Frontiers in Public Health, 2025)
BackgroundCardiovascular Diseases (CVD) remain a leading threat among aging populations globally, with Cardiovascular Health (CVH) trajectories shaped by cumulative exposures across the life course. Understanding these life-course connections is urgent to inform equitable geriatric care strategies.ObjectiveThis study aims to examine the long-term trajectories of CVH and the association between Childhood Access to Healthcare (CAH) and CVH trajectories in Chinese older adults.MethodsData were obtained from Chinese Longitudinal Healthy Longevity Study (CLHLS). A composite CVH score was established based on the American Heart Association’s (AHA) guidelines. Group-Based Trajectory Modeling (GBTM) was employed to identify distinct CVH trajectories over time. Multi-logistic regression was used to analyze the association between CAH and CVH trajectories. To minimize potential confounding and selection bias, entropy balancing was applied to balance covariates between the treatment and control groups.ResultsThree distinct CVH trajectories were identified: Low-rapid decline (25.2%), Moderate-stable (65.7%), and High-stable (9.1%). Compared with high-stable trajectory, individuals with CAH were associated with lower likelihood in moderate-stable trajectory (Adjusted and balanced OR = 0.61, 95% CI: 0.44–0.85, p < 0.01) and low-rapid decline trajectory (Adjusted and balanced OR = 0.63, 95% CI: 0.44–0.90, p < 0.05), suggesting that CAH was associated with more favorable long-term CVH outcomes. Subgroup analysis indicated that the association was generally stable across different populations.ConclusionCAH significantly influences the long-term CVH trajectories of older adults in China. These findings underscore the need for public health interventions that prioritize childhood healthcare access to reduce the burden of CVD in the aging population.